582. REPORT ON A 42 YEAR EXPERIENCE WITH THE LAPAROTOMIC/LAPAROSCOPIC HELLER-DOR OPERATION PERFORMED WITH INTRAOPERATIVE MANOMETRY FOR ESOPHAGEAL ACHALASIA. (24th September 2022) - Tassi, Valentina; Lugaresi, Marialuisa; Baldi, Fabio; Mattioli, Bendetta; Daddi, Niccolò; Pilotti, Vladimiro; Mattioli, Sandro
Abstract: In 1979 our surgical group proposed the Heller-Dor operation (HD) to accomplish new concepts of surgical pathophysiology: to abolish the lower esophageal sphincter with the division of the U-and sling fibers of the lesser gastric curvature, to prevent GER with an effective but not too effective partial fundoplication which protects the myotomy surface. Aim is to report very long-term results of the treatment of esophageal achalasia with the Heller-Dor operation performed with intra operative manometry. In the period 1979-2021 HD was in first instance adopted in 202 patients (97 men; median age 45 years; IQR 31–59) in laparotomy (L-HD) and in 162 (79 men; age 48 years; IQR 35–63) in laparoscopy (V-HD). At intraoperative manometry, the complete abolition of the high-pressure zone was always obtained and the Dor length and pressure were trimmed according to reference values. Follow-up consisted of interview, endoscopy and barium swallow performed every 3 years. The overall outcome was graded from excellent to poor according to the severity of symptoms and esophagitis. Median follow-up was 14.8 years in HD, 7.5 years in V-HD (p<0.001). Esophageal diameter and residual barium column decreased substantially during the first 3 years after the operation, but not successively. In the L-HD group poor results were 22 (10.9%): due to esophagitis in 17 (8.4%) and to recurrent dysphagia in 5 (2.5%). In V-HD, 4 (2.5%) had esophagitis and 2 (1.2%) severe dysphagia. Outcome was satisfactory in 89% of L-HD and in 96% of V-HD (p<0.001). Postoperatively, according to the Kaplan Mayer curve, dysphagia, reflux symptoms and esophagitis occurred within 60-65 months after surgery. Timing of dysphagia relapse and post-myotomy reflux occurrence indicate that after five years, surgical results can be considered definitive. The 96% of satisfactory results we achieved with VL-HD, at a median follow-up time of 8 years, shows the potentiality of this surgical technique. In our experience, the learning process, not the follow-up length or the laparotomy/laparoscopy method is the cause of improved results of the laparoscopy HD.